Pertumbuhan dan produksi sawi manis (Brassica juncea L.) pada berbagai dosis pupuk kompos ternak sapi dan pupuk N, P dan K - Sanusi, Ahmad; Setyono, Setyono; Adimihardja, Sjarif Avitidjadi (Universitas Djuanda Bogor, 2015)
The study was aimed at assessing the effects of the application of different rates of cattle compost manure and N, P, K fertilizer on the growth and production of mustard greens. The study was done from May to June 2013 at Agrotechnology Trial Farm of Djuanda University. A factorial completely randomized design with two factors was used. The first factor was cattle compost manure in four levels, namely 0 ton/ha (R), 5 ton/ha (0,5 R), 10 ton/ha (R), and 15 ton/ha (1,5 R). The second factor was N, P, K fertilizer in four levels, namely 0 kg/ha (0 R), Urea 187 kg/ha + SP-36 155.5 kg/ha + KCl 112 kg/ha ( 0.5 R), Urea 374 kg/ha + SP-36 311 kg/ha + KCl 224 kg/ha ( R), and Urea 561 kg/ha + SP-36 466.5 kg/ha + KCl 336 kg/ha ( 1.5 R). Results showed that no interaction effect was found on all parameters measured except on the shoot diameter at 2 weeks after planting (WAP). Increasing rates of cattle compost manure did not give significant effects on all parameters measured except on number of leaves at 2 WAP. Increasing rates of N,P,K fertilizer were found to significantly increase the growth and production of mustard greens. This positive effects were found on plant height, number of leaves, and trunk diameter at 2, 3, and 4 WAP and shoot diameter at 3 and 4 WAP. Shoot wet and dry weights of plants in 1.5 R, N, P and K were significantly higher than those in other treatments.Keywords: Brassica juncea L., cattle manure,N, P, and KÂ